Effect of Hydrodynamic Environment on Tablet Dissolution Using Flow-Through Dissolution Apparatus - Wu, Yan; Ghaly, Evone S. (Puerto Rico Health Sciences Journal, 2006)
The main objective of this research is to investigate the principles underlying the dissolution process, study the phenomena of drug release in laminar flow, and better understand the effect of hydrodynamic condition on drug dissolution, in order to predict drug dissolution from a solid dosage form. Two drug models were selected, theophylline (Class I) and naproxen (Class II), and were formulated into conventional tablets containing 105 mg theophylline or 300 mg naproxen using wet granulation method. Additionally theophylline (105 mg) and naproxen (300 mg) matrices containing 30% hydroxypropylmethylcellulose (HPMC) polymer were prepared by direct compression and tested for dissolution using both USP II and IV dissolution apparatus. Tablets were tested for dissolution (USP IV) using different cell diameter, flow rate, and different position of the tablet inside the cell. In general, the drug dissolution at a given time is a direct function of the flow rate, increasing the flow rate increases drug release. The use of a small cell resulted in faster drug dissolution and higher Reynold’s Number than using a large cell. Tablet position in the cell, also has an effect on drug dissolution, inserting the tablet in a horizontal position inside the cell gave faster dissolution than a vertical position. The hydrodynamic conditions did not affect the drug dissolution from HPMC controlled release tablets indicating that the drug dissolution is controlled by the matrix. An equation to predict drug dissolution from conventional tablets was established: Sh=-21.36+10.58Re1/2 where R2=0.98. This study demonstrated that hydrodynamic conditions, and type of dissolution testing apparatus used have an effect on dissolution rate, mass transfer rate, and film thickness underlying dissolution process.